Hygienic production practices and microbial evaluation of cow milk quality in District Gilgit - Ishrat Roomi,; Azhar Hussain,; Sartaj Khalil,; Shahnawaz Laqdoom,; Waqar Younus,; Ghulam Abbas, (International Journal of Pathology, 2024)
Background: Dairy cow’s raw milk may get contaminated by pathogens released by diseased animals, bacteria from the environment, or germs from the udder. Insufficient hygiene on the udder and teat surfaces, as well as contaminated milking equipment, can transfer environmental organisms into the milk.  Methods: To examine the practices of hygienic cow milk production, a study was conducted with 175 respondents from District Gilgit, who were selected to evaluate their understanding and implementation of hygienic milk production methods. The participants were interviewed to determine their level of understanding. In addition, fifty milk samples were collected from the producers to assess the microbiological purity of the milk. Results: The findings revealed that a significant proportion of milk producers neglected or were unaware of essential hygiene practices, such as washing hands, udders/teats of cows, and milking utensils before milking. The predominant water sources used were tap and stream, with the barn conditions largely being dusty despite daily cleaning efforts by most respondents. It was observed that milk processing and refrigeration post-milking were common practices, though a minority reported using injections and supplements preceding milking activities. The quality of milk was evaluated using the Methylene Blue Reduction Test (MBRT), Total Bacterial Count (TBC) and Total Coliform Count (TCC). Analytical results indicated MBRT durations ranging from 1 to 8.5 hours, with TBC and TCC levels extending from 2.16x106 to 1.008x107 and 3x105 to 6.56x106, respectively. Most of the milk samples were of fair quality having average MBR time and the TBC and TCC have values above the upper limits set to 105.Conclusion: The finding identified inadequate hygiene, low water quality for cleaning, and poor barn conditions as the primary factors contributing to the low milk quality in Gilgit.  Therefore, it is essential to enhance the hygienic dairy practices and promote public health.